(untitled) (Annual of the Faculty of Philosophy in Skopje, 2014)
The purpose of this research is to determine whether there is a difference in the auto perception of educational styles of parents and social perception of educational styles of children at social risk. For this purpose it is used a convenience sample of 195 respondents, 65 children at social risk (38 female and 27 male subjects ) and 130 parents of children at risk. To measure the educational styles of parents by adolescents and parents was used EMBU questionnaire, which consists of five subscales: rejection, overprotection, emotional warmth, inconsistency and favoritism. The results showed no difference in auto perception of mother and social perception of children of the educational styles rejection and emotional warm th, and that there is a difference in the educational styles rejection and emotional warmth between mother and father of an adolescent.